Adaptive fuzzy dynamic surface sliding mode control of large-scale power systems with prescribe output tracking performance. (April 2020) - Zhu, Guoqiang; Nie, Linlin; Lv, Zhe; Sun, Lingfang; Zhang, Xiuyu; Wang, Chenliang
Abstract: This paper focuses on an adaptive fuzzy based dynamic surface sliding mode control (ADSSMC) strategy for multi-machine power systems with SVC. The main characteristics of the proposed ADSSMC strategy are: (1) System robustness and the convergency speed of all surface error are enhanced by combining dynamic surface control with sliding mode, leading to the structural complexity of the controller in backstepping control scheme is eliminated; (2) By introducing an error performance conversion function, the errors of desired trajectory and system output are always within a predetermined range; (3) In the adaptive regulation laws, the number of estimated parameters of the control system is significantly reduced due to the utilization of the estimations of weight vector norm instead of the weight vectors itself. The stability analysis proves that the proposed ADSSMC control strategy can guarantee the boundaries of all signals in the closed-loop control system. Experimental results verify the effectiveness of the proposed ADSSMC scheme. Highlights: Design of adaptive dynamic surface sliding mode controller for a large scale power system. Introducing an error transform function to guarantee the output tracking performance. By updating the norm of the weight vector of FLSs to reduce the computational burden. The effectiveness of the proposed control scheme is verified by the experiment of hardware-in-the-loop simulation platform.